PENGELOLAAN KUALITAS UDARA DI PERKOTAAN - Suyanto, Hadi (Gema Teknologi, 2011)
Hadi Suyanto, in this paper explain that to avoid global warming and climate change effect, re-greening program at the open and dry area need to be established, this also to generate fresh temperature and improve health and comfort. Develop and enlarge green zone and public zone as part of air quality management that have social and environmental function, and not just as an esthetically function. Keyword: Air Quality, re-greening